Performance Analysis of Current Control Strategies for Hybrid Stepper Motors - Fabio Bernardi; Emilio Carfagna; Giovanni Migliazza; Giampaolo Buticchi; Fabio Immovilli; Emilio Lorenzani (IEEE Open Journal of the Industrial Electronics Society)
Hybrid stepper motors are widespread in industrial automation due to their robustness and high torque performance in low speed range, e.g. 3D printers, pick and place, and generally in many low power positioning applications. In order to increase the efficiency and dynamic performance, current/speed/position closed loop controls are implemented for high performance sensored stepper drives. The main challenge comes from the high number of magnetic poles which these motors feature, increasing the ratio between the fundamental and switching frequency. This paper critically evaluates four current control structures based field oriented control: classic PI regulators, sliding mode control, deadbeat predictive current control and model predictive current control. Simulations and experimental results aim to evaluate the dynamic performance, phase current amplitude and distortion in order to support the critical comparison.